A NEW SPECIES OF CATASETUM (ORCHIDACEAE) FOR THE STATE OF MATO GROSSO, BRAZIL - Petini-Benelli, A.; Grade, A. (Edinburgh Journal of Botany, 2008)
A new species of Catasetum Rich. ex Kunth (Orchidaceae), Catasetum apolloi Benelli & Grade, from the municipality of Carlinda in the State of Mato Grosso, Brazil is described and illustrated. The plant was discovered in a pasture near the Teles Pires River growing epiphytically under the palm Maximiliana regia Mart. A discussion and consideration of possible related species is presented.